2021
DOI: 10.1002/ajb2.1636
|View full text |Cite
|
Sign up to set email alerts
|

Candidate genes and signatures of directional selection on fruit quality traits during apple domestication

Abstract: PREMISE During plant domestication, traits can be subject to a variety of types of selection, ranging from strong directional selection for traits such as seed or fruit size to diversifying selection for traits like color or flavor. These types of selection interact with other evolutionary processes including genetic bottlenecks and interspecific gene flow to generate different levels of genetic diversity across the genome and at target genes in domesticated lineages, but little is known about the impacts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 69 publications
(106 reference statements)
0
9
0
Order By: Relevance
“…Moreover, according to the autochthone accessions from the different germplasm collections around the world, domestication and breeding could have caused diversity loss. Nevertheless, regardless of the many decades of domestication of Malus × domestica and its clonal propagation, there is no proof that domesticated apples have shown a genetic bottleneck in contrast with Malus × sieversii [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, according to the autochthone accessions from the different germplasm collections around the world, domestication and breeding could have caused diversity loss. Nevertheless, regardless of the many decades of domestication of Malus × domestica and its clonal propagation, there is no proof that domesticated apples have shown a genetic bottleneck in contrast with Malus × sieversii [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 21 misidentified and nine pure species PI accessions from the NPGS apple collection were tested for resistance levels to blue mold considering them to all be pure M. sieversii (Janisiewicz et al, 2008), and several accessions exhibiting moderate levels of resistance were hybrids and M. domestica in our results. Although Wedger et al (2021) used NPGS apple collection materials that were considered pure according to previous work (Gross et al, 2012), seven of the 15 M. sieversii individuals that study sampled from the NPGS were not pure species representatives according to the present analysis. In contrast, mapping population GMAL 4593 was created with parent PI 613981 (Desnoues et al, 2018), a M. sieversii pure species representative.…”
Section: Discussionmentioning
confidence: 99%
“…M. sieversii germplasm accessioned into the NPGS has been distributed as budwood of accessions resulting from imported budwood of wild trees considered “elites”, budwood of accessions grown from wild-collected seeds, and seed from crossing among wild accessions grown ex situ. These materials have subsequently been used to determine genetic relationships between M. domestica cultivars and M. sieversii ( Robinson et al., 2001 ; Gharghani et al., 2009 ; Nikiforova et al., 2013 ; Duan et al., 2017 ; Wedger et al., 2021 ), to evaluate phenotypic diversity of traits ( Janisiewicz et al., 2008 ; Fazio et al., 2009 ; Bassett et al., 2011 ; Jurick et al., 2011 ; Van Nocker et al., 2012 ; Fazio et al., 2014 ; Maguylo and Bassett, 2014 ; Harshman et al., 2017 ; Watts et al., 2021 ; Davies et al., 2022 ), and to identify QTLs and novel alleles ( Xu et al., 2012 ; Wisniewski et al., 2020 ; Singh et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed evidence of selection during apple domestication, e.g. , for fruit size ( Yao et al 2015 ; Duan et al 2017 ), fruit quality traits ( Wedger et al 2021 ), metabolite content ( Khan et al 2014 ) or disease-related genes ( Singh et al 2019 ). However, little information is available about the genomic consequences of the more recent apple improvement and the resulting genetic differences between genetic resources and modern cultivars.…”
Section: Discussionmentioning
confidence: 99%